On a small collection of linyphiid spiders from mountain Phoenix, Liaoning Province, China, with the description of a new species (Linyphiidae) - Tanasevitch, Andrei V.; Marusik, Yuri M. (Zootaxa, 2024)
A small series of spiders collected from a low mountain Phoenix in Liaoning Province of China, contains five linyphiid species, one of which, Platyspira scissa sp. nov. (♂, ♀), is described as new. The new species is similar to P. tanasevitchi Song & Li, 2009, known from caves in Guizhou Province, China. Habitus and copulatory organs of both sexes are illustrated for the new species, as well as for “Doenitzius” pruvus Oi, 1960. The taxonomic position of the genus Doenitzius Oi, 1960 is discussed. Distribution of each species is commented on.